A combined process model for wastewater treatment based on hydraulic retention time and toxicity inhibition. (July 2023) - Wei, Tuo; Ban, Zixin; Ke, Xiong; Chen, Acong; Guan, Xianghong; Gan, Haibo; Pan, Jiamin; Li, Zemin; Wei, Cong; Qiu, Guanglei; Wu, Haizhen; Wei, Chaohai
Abstract: Hydraulic retention time (HRT), as an important parameter in the wastewater treatment process, has a great impact on water quality and energy consumption. With the rapid advances in computer technology and deepened understanding of in microbial metabolism, a series of activated sludge models (ASMs) have been developed and applied in wastewater treatment. However, ASMs simulation based on the nexus of HRT, water treatment process, water quality and energy consumption has yet to be verified. In this study, HRT was creatively linked to water treatment process variation. And a novel combined process model (CPM) was developed based on the operational data and treatment performance data from 4 full-scale coking wastewater treatment processes. In the CPM, an array of biological treatment processes were represented by setting the HRT in respective treatment units of the anaerobic-oxic-hydrolytic & denitrification-oxic (A/O/H/O) process. The relationships between HRT, effluent quality and energy consumption were systematically analyzed. Results showed that: (i) for A/O/H/O process, the HRT of first oxic (O1) reactor has a key effect on the effluent water quality and energy consumption, while the impact of the anaerobic (A) reactor HRT was limited; (ii) the O/H/O process has a clear advantage in treating coking wastewater due to the carbon removal and detoxification function of O1 reactor; (iii) the lowest energy consumption (with the total system HRT below 210 h) to meet the biological effluent quality requirements (COD = 200 mg/L, TN = 50 mg/L) is 4.429 kWh/m 3 . Since the CPM could effectively work out the optimal process configuration and break the boundaries between HRT and process variation, it has enormous potential to be extended to the design of other wastewater treatment processes. Graphical abstract: Image 1 Highlights: A novel modeling idea for wastewater biological treatment process selection or design. The relationship between hydraulic retention time, water quality, and energy consumption was revealed. The boundaries between hydraulic retention time and process variation can be broken.